Pharmacological Evaluation of Different Extracts of Asparagus officinalis (Asparagaceae) as an Analgesic, Anti-Inflammatory and Anti-arthritic Agent in Rats - Satish Kumar; Pratima Srivastava; Sumeet Gupta; Meenakshi Dhanawat; Sapna Rani; Basiru Olaitan Ajiboye; Rupesh K Gautam (Pharmacognosy Research, 2023)
Background: To treat the joint pain arial part of Asparagus officinalis (asparagus) has historically been used. However, its efficacy for rheumatoid arthritis has not been pharmaceutically evaluated. We explore the phytochemical analysis anti-inflammatory, analgesic and anti-arthritic activity of petroleum ether, ethanol and aqueous extracts of Asparagus officinalis aerial part. Materials and Methods: Tail- flick method was used to evaluate the analgesic activity anti-inflammatory activity was carried out using paw oedema induced with carrageenan and CFA induced arthritic model was used to evaluate the potential in anti- arthritic activity in rats. The Petroleum ether, ethanolic and aqueous extracts were dosed orally in three divided doses (75, 150 and 300 mg/ kg). For anti- inflammatory and analgesic activity diclofenac sodium at 10 mg/kg was used as standard, whereas in anti-arthritic model prednisolone at 5 mg/kg and methotrexate at 0.5 mg/ kg were used as standard. One-way ANOVA followed by Dunnett’s multiple range test were used to analyse statistical significance between means. Results: The results revealed a dosecontrolled anti-inflammatory, anti-arthritic effect with different extracts whereas at some extent analgesic activity was observed. Four compounds were present and confirmed by LCMS/MS. The CFA model's findings showed improved defence against arthritic lesions and changes in body weight. Additionally, Asparagus officinalis significantly improved rheumatoid factor, changed WBCs, and favourably altered radiographic and histological alterations. Conclusion: The findings indicate that Asparagus officinalis is a strong anti-arthritic and anti-inflammatory compound that may be suggested for the treatment of both chronic and acute inflammation.
Keywords: Carrageenan; Chemical constituents; LCMS/MS; Rheumatoid Arthritis; Sparrow grass.